Finding the Personal Voice in Filmmaking - Knudsen, Erik (Springer International Publishing, 2018)
This book philosophically and creatively examines ways in which independent filmmakers may explore, through practice, the discovery and development of a personal voice in the making of their films. Filmmaker and academic, Professor Erik Knudsen, uses a combination of autoethnographic experience derived from his own filmmaking practice and new insights gained from a series of ethnomediaological StoryLab workshops with independent filmmakers in Malaysia, Ghana and Colombia to drive this innovative examination. The book contextualises this practice exploration within an eclectic psychological and philosophical framework that ranges from Jungian psychological theories of the collective unconscious to Sheldrakian scientific theories of morphic resonance, from Christian mystical ideas about creative motivation to structuralist theories that underpin our linguistic understanding of story and narrative. Why should we create? What is a creative act? This in-depth study tackles these questions by examining the early ideation stages of cinematic expression and ultimately seeks to understand the practical ways in which ideas are shaped into stories and narratives. .